Surgical versus non-surgical management of patients soon after acute myocardial infarction. Issue 5 (November 1985) - Brower, R W; Fioretti, P; Simoons, M; Haalebos, M; Rulf, E N; Hugenholtz, P G
Abstract : Of 510 patients admitted to hospital with acute myocardial infarction, 34 had coronary artery bypass grafting before discharge (6-43 days (median 20) after infarction). The patients who were given grafts generally had a smaller infarction with less functional impairment than the 476 patients who were not. The outcome of coronary artery bypass grafting was investigated in a retrospective matched pair study. Patients were matched on the basis of the presence of postinfarction angina, left ventricular ejection fraction, location of the infarction, peak creatine kinase activity, Killip clinical class, and severity of coronary disease with 34 patients who were given medical treatment only. At one year follow up fewer of the operated patients had symptoms than did the matched non-operated patients. Survival at one year in the operated and non-operated groups respectively was 94% vs 91%; angina within one year occurred in 3% vs 68%; congestive heart failure in 3% vs 6%; and 0% vs 32% were referred for later bypass grafting or coronary angioplasty. It is concluded that coronary artery bypass grafting can be performed safely soon after myocardial infarction provided that left ventricular function is not seriously compromised. Such treatment is more effective than medical treatment for relief of angina during the first year after infarction.